2021
DOI: 10.3390/min11090967
|View full text |Cite
|
Sign up to set email alerts
|

Response and Dynamic Change of Microbial Community during Bioremediation of Uranium Tailings by Bacillus sp.

Abstract: Bacillus sp. is widely used in the remediation of uranium-contaminated sites. However, little is known about the competitive process of microbial community in the environment during bioremediation. The bioremediation of uranium tailings using Bacillus sp. was explored, and the bacterial community was analyzed by high-throughput sequencing at different stages of remediation. Bacillus sp. reduced the leaching of uranium from uranium tailings. The lowest uranium concentration was 17.25 μg/L. Alpha diversity revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…When the pH of the system is close to neutral, the microbial activity is higher under the premise that all other environmental conditions are consistent, thus increasing the higher stabilization rate of uranium. In addition, the control group (aseptic inoculation experiments) showed that the unstable uranium remained at a relatively high level after the leaching effect of medium in our previous study ( Tang et al, 2021 ). Therefore, it can be inferred that uranium conversion is mainly based on microbial metabolism.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…When the pH of the system is close to neutral, the microbial activity is higher under the premise that all other environmental conditions are consistent, thus increasing the higher stabilization rate of uranium. In addition, the control group (aseptic inoculation experiments) showed that the unstable uranium remained at a relatively high level after the leaching effect of medium in our previous study ( Tang et al, 2021 ). Therefore, it can be inferred that uranium conversion is mainly based on microbial metabolism.…”
Section: Resultsmentioning
confidence: 67%
“…The uranium tailings used in this experiment were collected from a uranium tailings repository located in Fuzhou city, Jiangxi Province, southeast of China. Moreover, the chemical properties of the sampled tailings were shown in our previous study (Tang et al, 2021), as U, Mn, Fe, Ca, and SO 4 2− were the main compositions. The sulfate-reducing bacteria and phosphate-solubilizing bacteria used in this study were preserved in the National Engineering Laboratory of Biohydrometallurgy, China.…”
Section: Methodsmentioning
confidence: 57%
See 1 more Smart Citation
“…Mine tailing samples were collected at three different tailing storage sites in Krugersdorp, Gauteng province, South Africa (mixed tailing and tailing A—26.132750, 27.711464, tailing B—26.133074, 27.767206, and tailing C—26.135979, 27.740172). A diagonal sampling method was used [ 25 ], and the samples were collected at various depths: depth 1: 0–15 cm, depth 2: 15–30 cm, and depth 3: 30–45 cm, while mixed tailings (mixed tailings before re-processing) were collected on the surface. Each depth’s samples were combined (for instance, all 0–15 cm depth samples were combined to form one sample per sampling site), and from each tailing storage site, a total of three samples were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…At present, there are many studies on the correlation between microbial community structure and environmental factors in uranium mining area (Cho et al, 2012;Green et al, 2012;Coral et al, 2018), including active acid leaching uranium aquifer (Coral et al, 2018), uranium-contaminated tailing ponds (Dhal, 2018), former leaching heap area (~26 years; Sitte et al, 2015), and decommissioned uranium mine aquifers characterized by NO 3 − and uranium contamination (Cho et al, 2012;Green et al, 2012). In addition, many studies have also reported the dynamic changes of microbial communities during bioremediation (Zhang et al, 2017;Tang et al, 2021). However, there are limited studies about the characteristics of microbial communities in groundwater of decommissioned acid in-situ uranium mine.…”
Section: Introductionmentioning
confidence: 99%